Efficiency of the Overlay Network Clustering based on the Locality Metric - Poryev, G.V. (Реєстрація, зберігання і обробка даних, 2011)
The method of estimating the efficiency of the overlay network clustering in the swarms of peer-to-peer networks is proposed. The brief overview of the locality metric as a topological distance substitute is given and using regional Internet registries as information sources for constructing the structural model of the network is substantiated. Запропоновано метод оцінки ефективності кластеризації оверлейних мереж у роях однорангових мереж. Подано огляд метрики локальності як заміни топологічної дистанції і обґрунтовано використання регіональних реєстрів Інтернет як джерел інформації для побудови структурної моделі мережі. Предложена обобщенная архитектура аналитической составляющей корпоративных информационно-аналитических систем (КИАС), отражающей ее основные компоненты по функциональному назначению для решения задач деловой аналитики, и определены основные направления развития компьютерных средств аналитической составляющей КИАС на основе задач деловой аналитики на современном этапе.